Composite odontoma with 23 denticles in a pediatric patient: A case report - Paôla Caroline da Silva Mira; Jéssica Silva Peixoto Bem; Andresa Vieira da Silva; Marcio Santos de Carvalho; Marcelo Rodrigues Azenha; Christiano Oliveira-Santos; Maria Bernadete Sasso Stuani; Carolina Paes Torres (Arbu Academic Publishing, 2021)
Compound odontoma is an odontogenic tumor of ectomesenchymal origin containing tooth-like structures. Occasionally, this lesion may trigger occlusal, phonetic, and aesthetic disorders. The aim is to report a case of a compound odontoma containing 23 denticles in the anterior region of the maxilla of an infant patient. A 12-year-old male patient was referred for orthodontic treatment at Ribeirão Preto School of Dentistry, University of São Paulo (Ribeirão Preto, Brazil) complaining of a large diastema between the upper central incisors. Panoramic radiograph revealed the presence of a radiopaque lesion with tooth-like structures surrounded by a radiolucent rim in the anterior region of the maxilla, associated with distal displacement of the left central incisor. Surgical approach under general anesthesia revealed and extracted 23 denticles. Post-operative Cone beam computed tomography (CBCT) confirmed removal of all denticles, and further orthodontic treatment could be planned. Multidisciplinary involvement of pediatric dentist, oral and maxillofacial surgeon, and orthodontist was essential to achieve full functional, aesthetic, and psychosocial success.